Evolution of performance traits on boars test stations in Santa Catarina - Costa, Cláudio Nápolis; Fávero, Jerônimo Antônio; Larrambebere, Walter H. Saralegui; Leitão, Geísa Ribeiro (Pesquisa Agropecuaria Brasileira, 2014)
Data from 1,016 boars of Landrace (465), Large White (407) and Duroc (144) breeds tested at four performance test stations in Santa Catarina from 1977 to 1981 were analysed to evaluate the effects of test station, breed, season, year tested within station and their interactions on final age (FA, age at 100 kg), average daily gain (ADG), food conversion (FC) and backfat thickness (BF). There were differences (P < 0.01) among test stations for FC and BF, and among breeds (P
Keywords: selection; test station; time trends